Deviant peer influences in programs for youth: problems and solutions - Dodge, Kenneth A.; Dishion, Thomas J.; Lansford, Jennifer E. (Duke series in child development and public policy, 2006)
The problem of deviant peer influences in intervention programs / Kenneth A. Dodge, Jennifer E. Lansford, and Thomas J. Dishion -- Deviant peer contagion in interventions and programs : an ecological framework for understanding influence mechanisms / Thomas J. Dishion and Kenneth A. Dodge -- Deviant peer effects : perspectives of an epidemiologist / James C. Anthony -- Assigning youths to minimize total harm / Philip J. Cook and Jens Ludwig -- Is deviant peer influence a problem and what can be done? : qualitative perspectives from four focus groups / Jennifer E. Lansford and Joel Rosch -- Deviant peer group effects in youth mental health interventions / Kenneth A. Dodge and Michelle R. Sherrill -- Deviant peer effects in education / Wendy M. Reinke and Hill M. Walker -- Peer effects in juvenile justice / D. Wayne Osgood and Laine O'Neill Briddell -- The effects of community-based group treatment for delinquency : a meta-analytic search for cross-study generalizations / Mark W. Lipsey -- Peer effects in neighborhoods and housing / Jacob Vigdor -- Iatrogenic outcomes of the child welfare system : vulnerable adolescents, peer influences, and instability in foster care arrangement / Melvin N. Wilson and LaKeesha N. Woods -- Peer effects in community programs / Jennifer E. Lansford -- Peer effects in naturally occurring groups : the case of street gangs / Malcolm W. Klein -- Research-based prevention programs and practices for delivery in schools that decrease the risk of deviant peer influence / Rebecca B. Silver and J. Mark Eddy -- Promising solutions in juvenile justice / Peter Greenwood -- Prevention approaches to improve child and adolescent behavior and reduce deviant peer influence / Emilie Phillips Smith, Jean E. Dumas, and Ron Prinz -- Promising solutions in housing and the community / Jens Ludwig and Greg Duncan -- Creating a legal and organizational context for reducing peer influence / Joel Rosch and Cindy Lederman -- A functional contextualist framework for affecting peer influence practices / Anthony Biglan, Jeffrey Sprague, and Kevin J. Moore -- Findings and recommendations : a blueprint to minimize deviant peer influence in youth interventions and programs / Thomas J. Dishion, Kenneth A. Dodge, and Jennifer E. Lansford